The Role Of Public Sector Audit In Improving Accountability And Transparency In Local Government Financial Management - Dito Aditia Darma Nst; Rania Rizqi; Llili Aprilliani; Ulfa Muharrammaini; Stefany Gabriella (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Public sector audit plays a strategic role in promoting accountability and transparency in the management of local government finances. Various problems in regional financial management, such as inaccurate recording, weak internal control systems, and low compliance with regulations, highlight the importance of audit as an effective oversight and evaluation mechanism. This study aims to analyze the role of public sector audit in enhancing accountability and transparency in local government financial management. The research employs a qualitative approach using literature review and document analysis, including audit reports of the Audit Board of Indonesia (BPK), regulations on regional financial management, and relevant previous studies. The results indicate that public sector audit significantly contributes to improving the quality of local government financial statements, strengthening internal control systems, and encouraging compliance with applicable laws and regulations. Furthermore, audit recommendations serve as an instrument for continuous improvement in regional financial management practices. However, the effectiveness of public sector audit is influenced by the commitment of local government leaders, the follow-up of audit recommendations, and the competence of financial management personnel. Therefore, strengthening the public sector audit function is essential to achieve transparent, accountable, and good governance–oriented local government financial management.